A structural equation model of financial risk tolerance in South Africa - Suné Ferreira; Zandri Dickason Koekemoer (Cogent Business & Management, 2020)
Modelling investor behaviour in the South African context is important for investment companies to profile their clients. Various factors can influence the risk tolerance of investors. For the purpose of this research article, the emphasis was placed on demographics, life satisfaction and how risk-taking behaviour and perception in several life domains influences risk tolerance. An electronic questionnaire was distributed to over 4 000 investors throughout South Africa. The final sample size was 1 065. Age and gender were found to significantly influence investor risk tolerance. A negative relationship was found between age and risk tolerance, indicative that risk tolerance decreases with age. Life satisfaction did also significantly contribute to predicting investor risk tolerance. The development of this risk tolerance structural equation model is unique in its existence, as it is the first model to incorporate demographics, life satisfaction, risk-taking behaviour and perception, and risk tolerance level in the South African context. As a result, these findings will make a significant contribution to the way financial investment companies profile their clients.
Keywords: D81; G11; J11; 650; gender; age; financial risk tolerance; life satisfaction; investors; South Africa